Human Resource Development Practices and Learning Quality: The Role of Teacher Digital Competence in Madrasah Education - Hotni Sari Harahap; Aini Safitri; Nurhalimah Harahap; Lia Saniah; Dedi Pepriaman (Department of Economics Education, Faculty of Economics, Universitas Negeri Makassar, 2026)
This study investigates how Human Resource Development (HRD) practices influence learning quality, with teacher digital competence positioned as a mediating factor in madrasah education in Medan City, Indonesia. The study employed a quantitative explanatory design with a cross-sectional survey approach. Data were collected from 212 madrasah teachers using structured questionnaires. The data were analyzed using Structural Equation Modeling based on Partial Least Squares (SEM-PLS) with SmartPLS to assess the measurement model, structural relationships, and mediation effect. The results show that HRD practices have a positive and significant effect on learning quality and teacher digital competence. Teacher digital competence also has a positive and significant effect on learning quality. Furthermore, the mediation analysis confirms that teacher digital competence partially mediates the relationship between HRD practices and learning quality. These findings indicate that HRD practices improve learning quality both directly and indirectly by strengthening teachers’ digital capabilities. study is limited to madrasah teachers in Medan City and uses a cross-sectional design, which may restrict generalizability and causal interpretation. Future research should involve broader geographical coverage, longitudinal data, and additional variables such as institutional support, leadership, or digital infrastructure. This study contributes to the HRD and educational technology literature by integrating HRD practices, teacher digital competence, and learning quality into a unified empirical model within the underexplored context of Indonesian madrasah education. The study highlights digital competence as a strategic mechanism through which teacher development programs enhance learning quality in religious-based educational institutions.